INCLUSIVE PRACTICE IN R. MACEDONIA AT THE BEGINNING OF EFFORTS - Atanasoska, Tatjana; Iliev, Dean; Andonovska Trajkovska, Daniela; Seweryn Kuzmanovska, Marzanna (European Scientific Journal, ESJ, 2014)
Inclusive education is priority in many educational systems. It seems that educational process could not be effective and successful if it is not inclusive one. Educational policy demands creating inclusive practice which means that every one would find his place and could be treated according to different needs that pupils have. It is not easy to develop educational philosophy and to implement it. On that way there are any obstacles, challenges, but the way is the only one. Those decades are dedicated to efforts to make educational process and system inclusive one. Every country has his story. We share our story so that we can collect suggestions and offer experience for all who must follow this way.